3, 4-Donor- and 2, 5-acceptor-functionalized dipolar siloles: synthesis, structure, photoluminescence and electroluminescence. Issue 20 (17th May 2017) - Lin, Gengwei; Chen, Long; Peng, Huiren; Chen, Shuming; Zhuang, Zeyan; Li, Yinghao; Wang, Bohan; Zhao, Zujin; Tang, Ben Zhong
Abstract : Novel siloles substituted with electron donors and acceptors at the 2, 3, 4, 5-positions exhibit aggregation-induced emission (AIE) and good electroluminescence properties. Abstract : Siloles are a group of outstanding silicon-containing five-membered heterocyclics with intense solid-state fluorescence and superior electron-transporting ability. However, most studies focus on functionalization at the 1, 1- and 2, 5-positions of siloles, and siloles functionalized with electron donor and acceptor moieties at the 2, 3, 4, 5-positions are scarcely investigated. Herein, two new silole derivatives functionalized with acceptors of cyano or dimesitylboryl groups at their 2, 5-positions and donors of diphenylamino groups at their 3, 4-positions are successfully synthesized and fully characterized via spectroscopy, thermal analysis, crystallography, electrochemistry and theory calculations. These two functionalized silole derivatives are thermally stable and exhibit aggregation-induced emission (AIE) characteristics with intense fluorescence in solid films. Their HOMO energy levels are increased because of the incorporation of diphenylamino groups, whereas they have lowered LUMO energy levels due to the additional electron acceptors. The application of these new siloles as light-emitting materials for OLEDs is evaluated, where the nondoped OLEDs based on them display good device performances. These dipolar siloles can be useful models to further understand the structure–property relationship of siloles and provide a useful design principle for solid-state luminescent materials.